LEGAL PROTECTION OF CONSUMERS IN ELECTRONIC TRANSACTIONS: ITS IMPLEMENTATION IN THE LOCAL ECONOMIC SECTOR OF TOMOHON: Perlindungan Hukum Konsumen dalam Transaksi Elektronik: Implementasinya di Sektor Ekonomi Lokal Tomohon - Cindy Mariam Magdalena Rantung (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to examine the implementation of legal consumer protection in electronic transactions within the local economic sector of Tomohon City. With the increasing use of digital platforms for commercial activities, it is essential to assess how existing regulations are understood and applied by both consumers and business actors in small urban areas. A mixed-methods approach was employed, combining quantitative data from a closed-ended questionnaire completed by 20 consumer respondents and qualitative data obtained through in-depth interviews with 10 MSME operators. The findings reveal a low level of consumer awareness regarding their rights under national laws such as Law No. 8 of 1999. Most consumers did not file formal complaints despite experiencing transactional issues, often due to lack of knowledge or perceived complexity of the process. On the business side, many MSMEs lacked understanding of their legal obligations and relied on platform-specific policies without verifying compliance with national regulations. Informal dispute resolution remained the preferred method among both parties. The study highlights a significant gap between regulatory frameworks and actual practices, emphasizing the need for targeted education and institutional support. To improve the digital transaction environment in Tomohon, local authorities should enhance consumer literacy and provide guidance for MSMEs on legal compliance. This research contributes to the understanding of digital consumer law implementation in non-metropolitan contexts and offers insights for policy development and capacity-building initiatives.